Análisis de amenazas y vulnerabilidades en la red wifi de la Prefectura de la Provincia de Los Ríos. - Bajaña Molina, Tatiana Liseth (2018)
In Ecuador, it is very common to observe an exponential increase in the use of Wireless Fidelity (Wi-Fi) networks; due to this factor, the contemporary society advances rapidly based on the benefits provided by the direct and indirect use of physical and logical equipment oriented to communications and telecommunications, contributing in a clear and specific way with technological development, knowledge transfer, renewal and innovation of the criteria of thought and therefore the development of the socio-political, cultural, academic and social environment. For this reason it is intended through this research to provide a balanced content with a case study that is part of the analysis of threats and vulnerabilities in the Wi-Fi network of the Prefecture of the Province of Los Ríos, entering into theories and methods of research that strictly adhere to the technique of observation, analysis and interpretation of results. When talking about innovation, reference will be made to the structuring of a technical guide to the behavior of the Wireless Fidelity (Wi-Fi) network of the Prefecture of the Province of Los Ríos at the moment there are incidents caused by threats, whether they are internal or external and in the same way identify which are the types of vulnerabilities and the degree of affectation to the infrastructure of the institution because of the adverse elements to its nature.